Significance of Islamic Religious Education Learning in Fostering Student Character - Laili, Nur (Education Achievement: Journal of Science and Research, 2024)
Islamic Religious Education (PAI) learning has a very important role in fostering student character at school. This article examines how PAI learning can contribute to students' character building through curriculum approaches, teaching methods, and social interactions in the school environment. Using qualitative methods and literature analysis, this study found that effective PAI learning can shape students' moral, ethical, and spiritual character, as well as increase their awareness of positive religious values. Islamic Religious Education learning has great significance in fostering student character. Through a structured curriculum, appropriate teaching methods, and positive social interactions, Islamic Education can shape students with good character in accordance with Islamic teachings. Cooperation between teachers, parents, and schools is needed to optimize Islamic Education learning and support students' character development.